Resident Memory-Like Tumor-Infiltrating Lymphocytes (TILRM): Latest Players in the Immuno-Oncology Repertoire - Smazynski, Julian; Webb, John R. (Frontiers in Immunology, 2018)
Resident memory T cells (TRM) are a recently identified subset of long-lived memory T cells that are characterized in terms of their unique surface phenotype combined with a non-recirculating pattern of localization to non-lymphoid, peripheral tissues. TRM have quickly become a key area of focus in understanding immune responses to microbial infection in so-called “barrier” tissues, and appear to be particularly critical for protection against repeat exposure at the same site. More recently, tumor-infiltrating T cells with canonical TRM features are being identified in human cancers, in particular cancers of epithelial origin, and their presence is broadly found to be associated with favorable long-term prognosis. Moreover, recent studies have shown that these “resident memory-like” tumor-infiltrating lymphocytes (referred to herein as TILRM) are uniquely activated in melanoma patients undergoing PD-1 directed checkpoint blockade therapy. Accordingly, there is much interest at present regarding the biology of these cells and their precise role in anti-cancer immunity. Herein, we review the current state of the literature regarding TILRM with a specific emphasis on their specificity, origins, and relationship to conventional pathogen-specific TRM and speculate upon the way(s) in which they might contribute to improved prognosis for cancer patients. We discuss the growing body of evidence that suggests TILRM may represent a population of bona-fide tumor-reactive T cells and the attractive possibility of leveraging this cell population for future immunotherapy.